Estudios en Festuca elevada (I). Modo de desarrollo y efecto del manejo en primavera - Manzano Ramos-Izquierdo, Juan A. (Pastos, 2011)
R E S U M E NLa influencia del manejo sobre el comportamiento de una pradera de festuca elevada, cv. S. 170, es el objeto de este estudio. Los seis tratamientos diferenciales fueron dos frecuencias de corte enprimavera por tres niveles de nitrógeno. Se estudian algunos aspectos del desarrollo de los tallos, y especialmente la posición del ápice en los tallos encañados. S U M M A R YDuring the spring of 1969 the tiller density per unit area, the pattern of stem development and the number of green leaves were measured in a three years old established of S. 170 Tall Fescue sward under different nitrogen and cutting conditions.Nitrogen in spring increased the tiller density under frequent cutting conditions, but it had no effect when a relatively mature silage cut was taken. Stem development was accompanied by a decline in total density and in the number of green leaves per tiller.Two to three weeks after stem extension began, total density of stem tillers stabilized and the first heads emerged, the first fully emerged appeared approximately two weeks later.